Isolation and characterization of the Drosophila melanogaster gene encoding translation-initiation factor eIF-2 . - Ye, X.; Cavener, D.R. (Gene, 1994)
Drosophila melanogaster cDNA clones encoding the beta subunit of translation initiation factor 2 (eIF-2) were isolated and sequenced. The longest cDNA predicts a protein of 312 amino acids (aa), which possesses a putative RNA-binding motif and a highly charged N-terminal region composed of three basic polylysine blocks. The aa sequence comparison of D. melanogaster eIF-2 beta with its human and yeast counterparts demonstrates a high degree of similarity, especially within the C-terminal region. Northern analysis indicates quasi-constitutive expression of eIF-2 beta throughout D. melanogaster development.